Apical root-end filling with tricalcium silicate-based cement in a patient with diabetes mellitus: A case report - Biočanin, Vladimir M; Milić, Marija; Vučetić, Milan; Baćević, Miljana; Vasović, Dina; Živadinović, Milka; Cetković, Dejan; Čalasan, Dejan; Brković, Božidar (Vojnosanitetski pregled, 2017)
Introduction. The material used for root-end filling has to be biocompatible with adjacent periapical tissue and to stimulate its regenerative processes. Tricalcium silicate cement (TSC), as a new dental material, shows good sealing properties with dentin, high compression strengths and better marginal adaptation than commonly used root-end filling materials. Although optimal postoperative healing of periapical tissues is mainly influenced by characteristics of end-root material used, it could sometimes be affected by the influence of systemic diseases, such as diabetes mellitus (DM). Case report. We presented apical healing of the upper central incisor, retrofilled with TSC, in a diabetic patient (type 2 DM) with peripheral neuropathy. Standard root-end resection of upper central incisor was accompanied by retropreparation using ultrasonic retrotips to the depth of 3 mm and retrofilling with TSC. Postoperatively, the surgical wound healed uneventfully. However, the patient reported undefined dull pain in the operated area that could possibly be attributed to undiagnosed intraoral diabetic peripheral neuropathy, what was evaluated clinically. Conclusion. Although TSC presents a suitable material for apical root-end filling in the treatment of chronic periradicular lesions a possible presence of systemic diseases, like type 2 DM, has to be considered in the treatment outcome estimation.